Perencanaan Tebal Perkerasan Kaku (Rigid Pavement) Pada Jalan Sukodadi – Plembon Kabupaten Lamongan Berdasarkan Manual Desain Perkerasan (MDP) 2024 - Akhmalunniam, Muhammad; Judiono, Judiono (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
The Sukodadi-Plembon road section is located in Sukodadi District, Lamongan Regency. This road is 5,361 meters long and 4.3 meters wide and serves as a connection to the Lamongan Regency national road, resulting in an increase in the volume of vehicles passing through every day. Until now, the only treatment carried out is maintenance and repair of damaged road surfaces. This treatment is considered ineffective because the repair results are not long-lasting and have not been able to overcome the increasing traffic congestion. Therefore, appropriate pavement re-design is needed to reduce road damage while increasing user comfort. The use of rigid pavement construction was chosen because it has a longer service life than the previous pavement. The slab thickness design refers to the 2024 Pavement Design Manual with a thickness of 150 mm, equipped with longitudinal shrinkage joints using 16 mm diameter tie bars and transverse joints with 24 mm diameter dowels.